A mixed methods protocol to develop a mental health awareness program among adolescents in rural based schools of Mopani District, South Africa - Mahada, Tshisikhawe; Tshitangano, T. G.; Mphasha, M. H. (Frontiers in Public Health, 2025)
BackgroundAdolescence is a critical transitional phase characterized by rapid developmental changes, which makes this age group more vulnerable to mental health challenges and disorders. Despite the South African governments’ effort to implement the Integrated School Health Policy (ISHP), the prevalence of depression, anxiety, and suicidal behavior continues to rise among adolescents in rural based secondary schools. Therefore, this protocol aims to develop an intervention program to promote mental health awareness among adolescents in rural based secondary schools of Mopani district, Limpopo province, South Africa.MethodsThe study will be conducted in three phases. Phase 1 will involve a quantitative approach (phase 1A), using a cross-sectional descriptive research design. Cluster sampling method will be used to select schools, followed by systematic sampling to select adolescents between 12 and 18. Simple random sampling will be used to select teachers. Structured questionnaires will be used to collect data that will be analyzed using Statistical Package for Social Sciences software version 24 for data analysis. Qualitative approach (phase 1B) using explanatory research design will follow, which will be dependent on quantitative data. Both purposive and Snowball sampling methods will be utilized to sample adolescents and teachers. Semi-structured interviews will be used to collect data that will be analyzed thematically. Phase 1c will involve the synthesis and integration of the study through strength, weakness, opportunities, threats analysis; where findings from both phases will be consolidated and synthesized into a cohesive whole. Phase 2 will involve the development of a program using a logic model. The program will be presented in a table format, outlining specific objectives, activities, and outcomes. Phase 3 will focus on the validation of the developed program using the Delphi technique. The study has been approved by the University of Limpopo Research Ethics Committee: TREC/189/2025: PG.DiscussionThis research addresses the Sustainable Development Goals (SDGs) 3 and 4, ensuring healthy lives and promoting inclusive education. The study’s findings will contribute to the development of a tailored program to promote mental health awareness among adolescents in rural-based secondary schools. The study’s results will also provide valuable insights for policymakers, educators, and mental health professionals.ConclusionThe conclusion and recommendations will be based on the findings of the study.